Single-Cell Monitoring of Activated Innate Immune Signaling by a d2eGFP-Based Reporter Mimicking Time-Restricted Activation of IFNB1 Expression - Thomsen, Emil Aagaard; Andersen, Sofie; Marqvorsen, Mikkel Haarslev Schröder; Skipper, Kristian Alsbjerg; Paludan, Søren R.; Mikkelsen, Jacob Giehm (Frontiers in Cellular and Infection Microbiology, 2022)
The innate immune system represents a balanced first line of defense against infection. Type I interferons (IFNs) are key regulators of the response to viral infections with an essential early wave of IFN-β expression, which is conditional, time-restricted, and stochastic in its nature. The possibility to precisely monitor individual cells with active IFNB1 transcription during innate signaling requires a robust reporter system that mimics the endogenous IFN-β signal. Here, we present a reporter system based on expression of a destabilized version of eGFP (d2eGFP) from a stably integrated reporter cassette containing the IFNB1 promoter and 3’-untranslated region, enabling both spatial and temporal detection of regulated IFNB1 expression. Specifically, this reporter permits detection, quantification, and isolation of cells actively producing d2eGFP in a manner that fully mimics IFN-β production allowing tracking of IFNB1 gene activation and repression in monocytic cells and keratinocytes. Using induced d2eGFP expression as a readout for activated immune signaling at the single-cell level, we demonstrate the application of the reporter for FACS-based selection of cells with genotypes supporting cGAS-STING signaling. Our studies provide a novel approach for monitoring on/off-switching of innate immune signaling and form the basis for investigating genotypes affecting immune regulation at the single-cell level.